Influenza virus: 16 years' experience of clinical epidemiologic patterns and associated infection factors in hospitalized children in Argentina. - Angela Gentile; Maria Florencia Lucion; Maria Del Valle Juarez; Ana Clara Martinez; Viviana Romanin; Julia Bakir; Mariana Viegas; Alicia Mistchenko (PLoS ONE, 2018)
Influenza is an important cause of acute lower respiratory tract infection (aLRTI), hospitalization, and mortality in children. This study aimed to describe the clinical and epidemiologic patterns and infection factors associated with influenza, and compare case features of influenza A and B.In a prospective, cross-sectional study, patients admitted for aLRTI, between 2000 and 2015, were tested for respiratory syncytial virus, adenovirus, influenza, or parainfluenza, and confirmed by fluorescent antibody (FA) or real-time polymerase chain reaction (RT-PCR) assay of nasopharyngeal aspirates.Of 14,044 patients, 37.7% (5290) had FA- or RT-PCR-confirmed samples that identified influenza in 2.8% (394/14,044; 91.4% [360] influenza A, 8.6% [34] influenza B) of cases. Influenza frequency followed a seasonal epidemic pattern (May-July, the lowest average temperature months). The median age of cases was 12 months (interquartile range: 6-21 months); 56.1% (221/394) of cases were male. Consolidated pneumonia was the most frequent clinical presentation (56.9%; 224/394). Roughly half (49.7%; 196/394) of all cases had previous respiratory admissions; 9.4% (37/394) were re-admissions; 61.5% (241/392) had comorbidities; 26.2% (102/389) had complications; 7.8% (30/384) had nosocomial infections. The average case fatality rate was 2.1% (8/389). Chronic neurologic disease was significantly higher in influenza B cases compared to influenza A cases (p = 0.030). The independent predictors for influenza were: age ≥6 months, odds ratio (OR): 1.88 (95% confidence interval [CI]: 1.44-2.45); p<0.001; presence of chronic neurologic disease, OR: 1.48 (95% CI: 1.01-2.17); p = 0.041; previous respiratory admissions, OR: 1.71 (95% CI: 1.36-2.14); p<0.001; re-admissions, OR: 1.71 (95% CI: 1.17-2.51); p = 0.006; clinical pneumonia, OR: 1.50 (95% CI: 1.21-1.87); p<0.001; immunodeficiency, OR: 1.87 (95% CI: 1.15-3.05); p = 0.011; cystic fibrosis, OR: 4.42 (95% CI: 1.29-15.14); p = 0.018.Influenza showed an epidemic seasonal pattern (May-July), with higher risk in children ≥6 months, or with pneumonia, previous respiratory admissions, or certain comorbidities.